P-553 Response to controlled ovarian stimulation and preimplantation genetic testing for molecular disease (PGT-M) outcomes for Myotonic dystrophy type I (DM1) : A French multicentric study. (30th June 2022) - Sonigo, C; Ranisavljevic, N; Guigui, M; Anahory, T; Mayeur, A; Moutou, C; Rongières, C; Reignier, A; Lefebvre, T; Girardet, A; Ray, P; Steffann, J; et al.
Abstract: Study question: Does ovarian response to controlled ovarian hyperstimulation (COH) is altered in female affected by DM1 ? Summary answer: Ovarian response to COH is not altered in female affected by DM1 as compared to partners of affected males What is known already: Myotonic dystrophy type 1 is the most common adult muscular dystrophy caused by a CTG trinucleotide repeat expansion which may expand across generation. As this pathology presents an autosomal dominant inheritance, PGT may be an option to achieve a pregnancy with healthy baby. There are conflicting reports about response to COH for affected female. Moreover, few data are available concerning the chance to have a healthy baby after PGT for couple with one member affected by DM1 Study design, size, duration: The present study is a retrospective observational study carried out from January 2006 through January 2020. This multicentric study was conducted in all the five centers performing PGT-M in France. Participants/materials, setting, methods: A total of 229 couples started at least one COH cycle for the PGT procedure. The patient carrying the mutation was the female for 178 couples and the male for the 51 others. Overall, 648 COH cycles started and 560 oocytes retrieval for subsequent PGT were performed (430 for affected female and 130 for affected male). Parameters of ovarian response and PGT outcomes were compared according to the member affected by DM1. Main results and the role of chance: Age and BMI at the first COH cycle were not significantly different between both group but female carried mutation presented lower AMH level than partner of affected male. The starting and total doses of gonadotrophin were significantly higher for mutated females. The number of retrieved and mature oocytes per cycle were not statistically different (12 [8–16] versus 11 [8–16] retrieved oocytes, p = 0.63 and 9 [6–13] versus 9 [6-13] mature oocytes, p = 0.73, respectively). In both group, more than 70% of oocyte retrieval led to embryo biopsy. The proportion of started cycle allowing the obtention of at least one healthy embryo was significantly lower when the female was affected with DM1 (58.6% vs 70.4%, p = 0.012 ). In the female affected group, 49.7% of the cycles with oocytes retrieval lead to a fresh embryo transfer and a subsequent live birth rate per transfer of 21.4%. These results were not statistically different from the couple with affected male (58.5% of cycles with fresh embryo transfer (p = 0.08) and 23.6% live birth rate per transfer). Overall, after fresh or frozen embryo transfer, 30.8% of females with DM1and 41.2% of parter of affected males had at least one live birth from PGT. Limitations, reasons for caution: This a retrospective study included patients who were selected ovarian reserve parameters before PGT process. Moreover, the large time of inclusion may influence our conclusion. Wider implications of the findings: Information provided herein extends knowledge about the current state of COH for DM1 affected female. Moreover, PGT results presented here allow to provide patients with proposer counseling before starting PGT process. Trial registration number: CEROG-2020-GYN-0603